2020
DOI: 10.5194/acp-20-3373-2020
|View full text |Cite
|
Sign up to set email alerts
|

Modeling stratospheric intrusion and trans-Pacific transport on tropospheric ozone using hemispheric CMAQ during April 2010 – Part 1: Model evaluation and air mass characterization for stratosphere–troposphere transport

Abstract: Stratospheric intrusion and trans-Pacific transport have been recognized as a potential source of tropospheric ozone over the US. The state-of-the-science Community Multiscale Air Quality (CMAQ) modeling system has recently been extended for hemispheric-scale modeling applications (referred to as H-CMAQ). In this study, H-CMAQ is applied to study the stratospheric intrusion and trans-Pacific transport during April 2010. The results will be presented in two companion papers. In this Part 1 paper, model evaluati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 65 publications
1
16
0
Order By: Relevance
“…Horizontal resolutions of d01, d02, d03, and d04 are 45 × 45, 15 × 15, 5 × 5, and 5 × 5 km, respectively. The top height of the model was lifted from 10 000 to 5000 Pa to explicitly treat transport in the lower stratosphere (Itahashi et al, 2020). The vertical layer heights were adjusted to be consistent with those of the Chemical Atmospheric Global Climate Model for Studies of Atmospheric Environment and Radiative Forcing (CHASER) (Sudo et al, 2002), which was used to provide boundary concentrations, to avoid numerical diffusions to adjacent layers.…”
Section: Model Configurationmentioning
confidence: 99%
See 1 more Smart Citation
“…Horizontal resolutions of d01, d02, d03, and d04 are 45 × 45, 15 × 15, 5 × 5, and 5 × 5 km, respectively. The top height of the model was lifted from 10 000 to 5000 Pa to explicitly treat transport in the lower stratosphere (Itahashi et al, 2020). The vertical layer heights were adjusted to be consistent with those of the Chemical Atmospheric Global Climate Model for Studies of Atmospheric Environment and Radiative Forcing (CHASER) (Sudo et al, 2002), which was used to provide boundary concentrations, to avoid numerical diffusions to adjacent layers.…”
Section: Model Configurationmentioning
confidence: 99%
“…Various improvements were applied to the original emission inputs used in the first phase of J-STREAM described in Chatani et al (2018b) based on the outcomes of the model inter-comparisons. Hemispheric Transport of Air Pollution (HTAP) emissions version 2.2 (Janssens- Maenhout et al, 2015) was used for anthropogenic sources and international shipping for Asian countries except for Japan. While the target year of HTAP v2.2 is 2010, the ratios of sectoral annual emissions reported by Zheng et al (2018) were multiplied for China, and those reported by the Clean Air Policy Support System (CAPSS) (Lee et al, 2011) were multiplied for South Korea, to represent the changes in the precursor emissions of recent years.…”
Section: Emission Inputsmentioning
confidence: 99%
“…How about the trans-Pacific transport? Anthropogenic emissions in China grew during the 2000s (Itahashi et al, 2014) and reached the highest levels in the world in 2010; however, substantial reductions have been measured by satellites since then (Irie et al, 2016;Krotkov et al, 2016;van der A et al, 2017;Itahashi et al, 2018). In addition, bottom-up emission inventories indicate that Chinese NO x emissions were reduced as a consequence of clean air actions (Zheng et al, 2018).…”
Section: Perspective On the Changes In Trans-pacific Transportmentioning
confidence: 99%
“…The Community Multiscale Air Quality (CMAQ) modeling system version 5.2 extended for hemispheric applications (H-CMAQ) (Sarwar et al, 2015;Xing et al, 2015a;Mathur et al, 2017;Itahashi et al 2020aItahashi et al , 2020b) is used to incorporate and assess the impacts from volcanic SO2 emissions. H-CMAQ is configured to cover the entire Northern Hemisphere, utilizing a polar stereographic horizontal discretization of 187×187 grid points with a grid spacing of 108 km and a terrain-following vertical coordinate system with 44 layers of variable thickness from the surface up to 50 hPa.…”
Section: Hemispheric Cmaq Modeling System and Its Set Upmentioning
confidence: 99%